Pemberdayaan Masyarakat Gampong dalam Mitigasi Bencana Berbasis Kearifan Lokal di Kota Langsa - Teuku Hasan Basri; Ilyas Ilyas; Bachtiar Akob; Nuraini Nuraini (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2025)
his study aims to describe community empowerment at the gampong level in disaster mitigation based on local wisdom in Langsa City, emphasizing the novelty of the local gampong context and the integration model between local wisdom and modern disaster mitigation approaches. Using a descriptive qualitative approach, the research was conducted in six gampongs in Langsa City, involving 18 key informants consisting of gampong officials, traditional leaders, and community members. Data were collected through in-depth interviews, field observations, and document analysis. The findings indicate that gampong communities possess strong social capital through mutual cooperation (gotong royong), customary deliberation, and the ability to interpret natural signs as part of traditional mitigation practices. Community empowerment is implemented through disaster awareness programs and environmental conservation activities; however, their implementation has not been evenly distributed across all gampongs. The main finding reveals that integrating modern disaster training with local wisdom significantly enhances community preparedness, coordination, and collective response during disaster events. The main challenges include limited continuous assistance and the gradual erosion of traditional values among younger generations. Therefore, this study provides practical implications that disaster mitigation policies at the gampong level should focus on strengthening local institutions and internalizing local wisdom into formal disaster management programs to achieve more effective and sustainable disaster mitigation.